The role of citizen-based monitoring practices in improving public service delivery in Africa: A review - Matlala, Lesedi Senamele (Edelweiss Applied Science and Technology, 2025)
This study reviews Citizen-Based Monitoring (CBM) as a participatory accountability mechanism through which communities monitor, evaluate, and influence government performance in Africa. It examines how CBM enhances public service delivery across key sectors. Guided by the PRISMA-ScR framework and a Population–Concept–Context approach, the scoping review systematically searched eight academic databases (Scopus, Web of Science, PubMed, Embase, Africa-Wide, CINAHL, PsycINFO, AJOL) and grey literature sources covering 2000–2025. Eligible studies reported empirical CBM initiatives directly involving citizens in monitoring public services or policies. CBM is most advanced in the health sector, particularly HIV, tuberculosis, and malaria programs, while applications in education, water, sanitation, and local governance are emerging. Common mechanisms include community scorecards, social audits, citizen report cards, and digital tools such as SMS and mobile platforms. CBM enhances accountability, responsiveness, and citizen trust when supported by strong institutional ownership and civil society–government collaboration. To sustain impact, CBM must be institutionalized within formal governance systems, supported by stable financing, inclusive design, and mechanisms that close feedback loops to ensure citizen evidence informs policy and service delivery decisions.